Intramedullary sarcoidosis of the cervical spinal cord. Issue 5 (May 1985) - Vighetto, A; Fischer, G; Collet, P; Bady, B; Trillet, M
Abstract : A 26-year-old male with a history of pulmonary sarcoidosis showed clinical, myelographic and intra-operative evidence of a C5-C6 spinal cord tumour, which was diagnosed by biopsy as a pure intramedullary granuloma. Among the 29 published cases of histologically proven cord sarcoidosis, only five presented with pure parenchymatous infiltration without meningeal involvement. Corticosteroids are the most useful therapy, and surgery is indicated only for minimal biopsy when the parenchyma is invaded.